History of Patient's Traumatic Experiences Before Entering a Psychiatric Hospital: A Narrative Review - Iyus Yosep; Rohman Hikmat; Meideline Chintya; Nanda Amilia; Widya Nurwulan (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2022)
Background: The phenomenon of mental disorders is a phenomenon that continues to grow and has an influence on various aspects of life. One of the causes of mental disorders is the experience of traumatic events. Objectives: The purpose of this literature study is to find out what traumatic experiences the patient had before entering a mental hospital. Methods: The design used the narrative review method. The article search method used CINAHL, Pubmed, and Sciencedirect. The inclusion criteria were articles in English, a span of 10 years, full text, qualitative and quantitative, and respondents were patients in a mental hospitals. Results: The number of articles found and analyzed in this literature study was 8 articles regarding the traumatic experience of patients before entering a mental home. Conclusion: The experiences of patients before entering a mental hospital include the experience childhood trauma, post-disaster trauma, emotional trauma, and physical trauma.